Convalescent Plasma Treatment for Moderate to Critical Ill COVID-19 Patients – A Safe but Futile Treatment: A Non-Randomized Comparative Study - Jatu Aphridasari; Bintang Soetjahjo; Agus Joko; Rina Sidharta; Harsini Harsini; Arifin Arifin; Septian Adi Permana; Kunti Saraswati; Artrien Adhiputri; Sri Marwanta; Abdurahman Laqif; Rivan Danuaji (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: In a number of cases of viral infection, convalescent plasma therapy has been effective. Reportedly, the use of convalescent plasma as a therapy for COVID-19 patients with severe and life-threatening disorders is beneficial at this time. This study aims to assess the effectiveness and safety of convalescent plasma transfusions in hospitalized COVID-19 patients. Subjects and Method: This was a clinical trial employing a non-randomized comparative study. A historical control group (21 samples) and convalescent plasma transfusions (21 samples) was selected consecutively from hospitalized COVID-19 patients between May 6th, 2020, and May 6th, 2021 at Dr. Moewardi General Hospital. We assessed and quantified viral clearance in the laboratory. Statistical analysis is performed in SPSS version 20.0. Results: Plasma was taken from fifteen convalescent donors. In the plasma convalescent treatment group, there was a statistically significant difference between outcome and severity degree (p = 0.005). In addition, there was a substantial discrepancy between the result group and the control group (p 0.005). Significant differences in post-treatment NLR between the control and treatment groups (p 0.005). In addition, there were statistically significant differences between the control and treatment groups in post-treatment hsCRP levels (p 0.005). In addition, there were statistically significant differences (p 0.005) between all groups' inflammatory markers and outcomes. Conclusion: Using convalescent plasma to treat patients with COVID-19 is a rather safe practice. Our analysis demonstrated that the administration of convalescent plasma did not enhance survival or clinical outcomes for COVID-19 patients with moderate to severe disease. Keywords: COVID-19, convalescent therapy, critical ill